Transgender Dependent Adolescents in the U.S. Military Health Care System: Demographics, Treatments Sought, and Health Care Service Utilization. Issue 5 (16th October 2018) - Van Donge, Nela; Schvey, Natasha A; Roberts, Timothy A; Klein, David A
Abstract: Introduction: Transgender and gender-diverse (TGD) youth are at greater risk for mental health and medical conditions than their cisgender peers; however, poor health outcomes and identity-based discrimination can be minimized in the context of optimal support. Approximately 1.7 million youth may be eligible for care covered by the Military Health System, which includes mental health and gender-affirming medications. The purpose of the current study is to identify sociodemographic characteristics, the psychosocial and behavioral risk profile, and health care utilization patterns of TGD dependent youth cared for in the U.S. military system to inform provider training and resource allocation. Materials and Methods: We performed a retrospective chart review by searching all medical records between July 1, 2014 and July 1, 2017 for diagnoses suggesting visits for TGD-services at a regional referral-based adolescent medicine clinic which cares for dependent children of active duty, activated selected reserve, and retired military service members between the ages of 9 and 24 years for a wide range of health care needs. Results: Fifty-three participants were included in this study. Sixty-four percent reported a transmasculine identity, 21% a transfeminine identity, and 15% a non-binary or undecided identity. The mean age at first gender-related visit was 14.5 years (SD 3.2). The mean number of primary care physicians and specialists seen by a given individual in a military treatment facility for any visit type since the implementation of the medical record system in 2005 was 12 (SD 6.8) and 10.2 (SD 7.8), respectively. Thirty-three percent of all patients assigned as female at birth were on testosterone therapy and 23% of all patients assigned as male at birth were on estrogen therapy at their most recent clinic visit. Twelve patients were undergoing pubertal suppression with an injectable or implantable gonadotropin-releasing hormone agonist. Seventy percent reported a history of suicidal ideation, 42% self-harm, 21% at least one suicide attempt, and 33% psychiatric hospitalization. Having strongly supportive parents was significantly associated with recognizing, disclosing and seeking treatment for gender nonconformity at an earlier age ( p s ≤ 0.03) and marginally associated with less likelihood of current suicidal ideation ( p = 0.06) compared to those with less supportive parents. Conclusions: This study elucidated the sociodemographic and behavioral risk profile of a sample of TGD youth in the MHS. Military and non-military health care providers across a broad spectrum of specialties should be knowledgeable about the unique psychosocial and medical needs, requisite sensitivity, and available referral options in the care of TGD youth. Assumptions about one's gender identity, sexual orientation, gender expression, or behaviors cannot be made based on birth-assigned sex. Further research is needed to investigate the health and wellbeing of TGD military-affiliated youth over time and to determine quality transgender-related services in support of this vulnerable and underserved population.